#### Quiz-summary

0 of 10 questions completed

Questions:

- 1
- 2
- 3
- 4
- 5
- 6
- 7
- 8
- 9
- 10

#### Information

Hello Aspirants,

Welcome to our official website **http://www.studyvirus.com** for important study materials,quizzes,current affairs,etc.We are providing the most important quizzes for all bank exams-SBI PO,SBI Clerk,IBPS PO,IBPS Clerk,IBPS RRB exams,Insurance and many more.All the quizzes are based on latest pattern.

In this series of quizzes,we will be providing most important questions on **Quadratic Equations** **(Inequalities)** which are usually asked in the exams.In Prelims Examination,usually 5-10 questions are asked from this topic.

All the best !

Get the best selling **Data Interpretation and Puzzle Pen Drive Course (350+ videos)** along with PDF and online quizzes.**Click here **

Click here for **Real Exam Pattern Based Test Series for Banking exams **(SBI,IBPS,Insurance,etc) at the most affordable price.

You have already completed the quiz before. Hence you can not start it again.

Quiz is loading...

You must sign in or sign up to start the quiz.

You have to finish following quiz, to start this quiz:

#### Results

0 of 10 questions answered correctly

Your time:

Time has elapsed

You have reached 0 of 0 points, (0)

#### Categories

- Not categorized 0%

⇒ Please share your marks in comment section.

⇒Ask your doubts in too in comment section,we will try our best to clear all your doubts.

Keep Working Hard and Never Give Up

- 1
- 2
- 3
- 4
- 5
- 6
- 7
- 8
- 9
- 10

- Answered
- Review

- Question 1 of 10
##### 1. Question

Directions:1-10)

**In the following questions, two equations I and II are given. You have to solve both the equations and g****ive Answer as,**- √(1225)x + √(1089) =0
- (625)
^{1/4}y + (343)^{1/3}= 0

CorrectI.√(1225)x + √(1089) =0

35x + 33 = 0

35x = -33

X= -33/35 = -0.94

II.(625)

^{1/4}y + (343)^{1/3}= 05y+7 =0

Y= -7/5 = -1.4

x>y

IncorrectI.√(1225)x + √(1089) =0

35x + 33 = 0

35x = -33

X= -33/35 = -0.94

II.(625)

^{1/4}y + (343)^{1/3}= 05y+7 =0

Y= -7/5 = -1.4

x>y

- Question 2 of 10
##### 2. Question

I. 25x

^{2}– 45x + 14 =0II.48y

^{2}-176y – 64 =0CorrectI.25x

^{2}– 45x + 14 =025x

^{2}– 10x – 35x + 14 =05x(5x-2) -7(5x-2) =0

(5x-7) (5x-2) = 0

X= 7/5 , 2/5 =1.4, 0.4

II.48y

^{2}-176y – 64 =048y

^{2}-192y +16y – 64 =048y(y-4)+16 (y-4)=0

(48y + 16) (y-4) =0

Y= – 16/48, 4 = -0.33, 4

Can’t be determined

IncorrectI.25x

^{2}– 45x + 14 =025x

^{2}– 10x – 35x + 14 =05x(5x-2) -7(5x-2) =0

(5x-7) (5x-2) = 0

X= 7/5 , 2/5 =1.4, 0.4

II.48y

^{2}-176y – 64 =048y

^{2}-192y +16y – 64 =048y(y-4)+16 (y-4)=0

(48y + 16) (y-4) =0

Y= – 16/48, 4 = -0.33, 4

Can’t be determined

- Question 3 of 10
##### 3. Question

- 72x
^{2}-177x +108 =0 - 5y
^{2}+ 24y + 27 =0

CorrectI.72x

^{2}-177x +108 =072x

^{2}-81x -96x +108 =09x(8x-9)-12(8x-9) =0

(9x-12)(8x-9)=0

X=12/9 , 9/8 =1.33, 1.125

II.5y

^{2}+ 24y + 27 =05y

^{2}+ 15y + 9y + 27 =05y(y+3)+9(y+3) =0

(5y+9) (y+3) =0

Y= -9/5 , -3 = -1.8, -3

X > y

IncorrectI.72x

^{2}-177x +108 =072x

^{2}-81x -96x +108 =09x(8x-9)-12(8x-9) =0

(9x-12)(8x-9)=0

X=12/9 , 9/8 =1.33, 1.125

II.5y

^{2}+ 24y + 27 =05y

^{2}+ 15y + 9y + 27 =05y(y+3)+9(y+3) =0

(5y+9) (y+3) =0

Y= -9/5 , -3 = -1.8, -3

X > y

- 72x
- Question 4 of 10
##### 4. Question

- x
^{2}-11x +30 =0 - y
^{2}-13y + 42 =0

CorrectI.x

^{2}-11x +30 =0x

^{2}-5x -6x +30 =0x(x-5)-6 (x-5) =0

(x-6) (x-5) =0

X=6, 5

II.y

^{2}-13y + 42 =0y

^{2}– 6y – 7y + 42 =0y(y-6)-7(y-6) =0

(y-7)(y-6) =0

Y= 7, 6

x ≤ y

IncorrectI.x

^{2}-11x +30 =0x

^{2}-5x -6x +30 =0x(x-5)-6 (x-5) =0

(x-6) (x-5) =0

X=6, 5

II.y

^{2}-13y + 42 =0y

^{2}– 6y – 7y + 42 =0y(y-6)-7(y-6) =0

(y-7)(y-6) =0

Y= 7, 6

x ≤ y

- x
- Question 5 of 10
##### 5. Question

- 25x
^{2}+32x -36 =0 - 57y
^{2}-25y-42 =0

CorrectI.25x

^{2}+32x -36 =025x

^{2}-18x + 50x -36 =0X(25x-18)+2 (25x-18)=0

(x+2) (25x-18) = 0

X =-2, 18/25 = -2, 0.72

II.57y

^{2}-25y-42 =057y

^{2}+38y-63y -42 =019y (3y+2)- 21(3y+2) =0

(19y-21) (3y+2) =0

y= 21/19, -2/3 = 1.105, -0.66

Can’t be determined

IncorrectI.25x

^{2}+32x -36 =025x

^{2}-18x + 50x -36 =0X(25x-18)+2 (25x-18)=0

(x+2) (25x-18) = 0

X =-2, 18/25 = -2, 0.72

II.57y

^{2}-25y-42 =057y

^{2}+38y-63y -42 =019y (3y+2)- 21(3y+2) =0

(19y-21) (3y+2) =0

y= 21/19, -2/3 = 1.105, -0.66

Can’t be determined

- 25x
- Question 6 of 10
##### 6. Question

I.2x^2 + 19x + 45 = 0

II.2y^2 + 11y + 12 = 0

CorrectI.2x^2 + 19x + 45 = 0

2 × 45 = 90 = (10 × 9)

(10 + 9 = 19) x = (-10/2), (-9/2) (dividing by co efficient of x^2 and changing signs)

x = -5, -4.5

II.2y^2 + 11y + 12 = 0

2 × 12 = 24 (8 × 3 = 24) (8 + 3 = 11)

y = (-8/2), (-3/2) ) (dividing by co efficient of y^2 and changing signs)

y = -4, -1.5

Hence x < y

IncorrectI.2x^2 + 19x + 45 = 0

2 × 45 = 90 = (10 × 9)

(10 + 9 = 19) x = (-10/2), (-9/2) (dividing by co efficient of x^2 and changing signs)

x = -5, -4.5

II.2y^2 + 11y + 12 = 0

2 × 12 = 24 (8 × 3 = 24) (8 + 3 = 11)

y = (-8/2), (-3/2) ) (dividing by co efficient of y^2 and changing signs)

y = -4, -1.5

Hence x < y

- Question 7 of 10
##### 7. Question

I.3x^2 – 13x + 12 = 0

II.2y^2 – 15y + 28 = 0

CorrectI.3x^2 – 13x + 12 = 0

12 × 3 = 36 (-9 × -4 = 36) (-9 – 4 = -13)

x = 9/3, 4/3 (dividing by co efficient of x^2 and changing signs)

x = 3, 4/3

II.2y^2 – 15y + 28 = 0

2 × 28 = 56 (-8 × -7 = 56)

(-8 -7 = -15) (Dividing by co efficient of y^2 and changing signs)

y = 4, 3.5

Hence x< y

IncorrectI.3x^2 – 13x + 12 = 0

12 × 3 = 36 (-9 × -4 = 36) (-9 – 4 = -13)

x = 9/3, 4/3 (dividing by co efficient of x^2 and changing signs)

x = 3, 4/3

II.2y^2 – 15y + 28 = 0

2 × 28 = 56 (-8 × -7 = 56)

(-8 -7 = -15) (Dividing by co efficient of y^2 and changing signs)

y = 4, 3.5

Hence x< y

- Question 8 of 10
##### 8. Question

I.x^2 = 16

II.2y^2 – 17y + 36 = 0

CorrectI.x^2 = 16

x = ±4

II.2y^2 – 17y + 36 = 0

2 × 36 = 72 (-9 × -8 = 72)

(-9 -8 = -17) y = 9/2, 8/2(dividing by co efficient of y^2 and changing signs)

y = 4.5, 4

Hence x ≤ y

IncorrectI.x^2 = 16

x = ±4

II.2y^2 – 17y + 36 = 0

2 × 36 = 72 (-9 × -8 = 72)

(-9 -8 = -17) y = 9/2, 8/2(dividing by co efficient of y^2 and changing signs)

y = 4.5, 4

Hence x ≤ y

- Question 9 of 10
##### 9. Question

I.6x^2 + 19x + 15 = 0

II.3y^2 + 11y + 10 = 0

CorrectI.6x^2 + 19x + 15 = 0

6 × 15 = 90 (10 × 9 = 90) (10 + 9 = 19)

x = -10/6, -9/6 (dividing by co efficient of x^2 and changing signs)

x = -5/3, -3/2 = -1.66, -1.5

II.3y^2 + 11y + 10 = 0

3 × 10 = 30 (6 × 5 = 30) (6 + 5 = 11)

y = -6/3, -5/2 (dividing by co efficient of y^2 and changing signs)

y = -1.6, -2

Hence x ≥ y

IncorrectI.6x^2 + 19x + 15 = 0

6 × 15 = 90 (10 × 9 = 90) (10 + 9 = 19)

x = -10/6, -9/6 (dividing by co efficient of x^2 and changing signs)

x = -5/3, -3/2 = -1.66, -1.5

II.3y^2 + 11y + 10 = 0

3 × 10 = 30 (6 × 5 = 30) (6 + 5 = 11)

y = -6/3, -5/2 (dividing by co efficient of y^2 and changing signs)

y = -1.6, -2

Hence x ≥ y

- Question 10 of 10
##### 10. Question

I.2x^2 – 11x + 15 = 0

II.2y^2 – 11y + 14 = 0

CorrectI.2x^2 – 11x + 15 = 0

2 × 15 = 30 (-6 × -5 = 30) (-6 – 5 = -11)

x = -6/2, -5/2 (dividing by co efficient of x^2 and changing signs)

x = 3, 2.5

II.2y^2 – 11y + 14 = 0

2 × 14 = 28 (-7 × -4 = 28) (-7 -4 = -11)

y = 7/2, 4/2 (dividing by co efficient of y^2 and changing signs)

y = 3.5, 2

Hence relationship cannot be established

IncorrectI.2x^2 – 11x + 15 = 0

2 × 15 = 30 (-6 × -5 = 30) (-6 – 5 = -11)

x = -6/2, -5/2 (dividing by co efficient of x^2 and changing signs)

x = 3, 2.5

II.2y^2 – 11y + 14 = 0

2 × 14 = 28 (-7 × -4 = 28) (-7 -4 = -11)

y = 7/2, 4/2 (dividing by co efficient of y^2 and changing signs)

y = 3.5, 2

Hence relationship cannot be established